Analyzing literal and non-literal meaning in poetry: “What if” by Claudia Rankine - Sinambela, Chintya A; Damanik, Bernieke Anggita Ristia (Nur Science Institute, 2025)
Literal language in poetry provides clarity and concrete imagery, while non-literal expressions reveal deeper psychological and cultural meanings. This combination enables readers to engage intellectually and emotionally, fostering a more profound, reflective, and empathetic experience. Using a qualitative descriptive method grounded in semantic theory, this study examines Rankine's use of metaphor, irony, symbolism, and conditional expressions to convey themes of identity, emotional conflict, and social tension. This study highlights how Rankine's layered language encourages multiple interpretations, reinforcing the emotional and thematic impact of the poems. Findings suggest that combining literal and figurative analysis in literary studies, particularly in an educational context, can enhance students' understanding and critical thinking skills. By examining how language shapes meaning, this research confirms the educational value of poetry in fostering interpretive skills and emotional awareness.